Sexual behaviour and desire to discuss mental health as reported by HIV-infected men who have sex with men. (February 2013) - Safran, M A; Hoover, K W; Tao, G; Butler, M O
We assessed sexually transmitted infection risk behaviours and desire to discuss mental health, as reported by 426 HIV-infected men who have sex with men receiving HIV care in eight urban clinics. Most of these patients (90%) had begun HIV care >1 year ago. In the past year, 74% had multiple sexual partners, 75% engaged in anal intercourse, 48% had >1 HIV-uninfected partner and 82% used illegal psychoactive drugs. Among those reporting anal intercourse, approximately 61 % reported using a condom during the most recent episode. Among all patients, 70% wanted to talk with their clinicians about how they felt mentally or emotionally. Using a two-tailed chi-squared test, we found that patients who engaged in unprotected receptive anal sex were more likely to want such a conversation than those who did not (80% versus 62%, P < 0.01); and those who engaged in unprotected insertive anal sex were also more likely to want such a conversation (81 % versus 63%, P < 0.01). The findings highlight the prevalence of risky sexual behaviour and of mental health concerns in the participating patient population. Patients reporting risky sexual behaviour were more likely to want to discuss how they felt mentally or emotionally than those not reporting such behaviour.